1968
DOI: 10.1038/bjc.1968.10
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral development of ovarian tumour in thymectomized Swiss mice following a single injection of 7,12-dimethylbenz(a)anthracene at neonatal stage

Abstract: Images Figs. 1-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1970
1970
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Subsequent studies have shown that the administration of DMBA by oral (Biancifori et al, 1961;Jull et al, 1966;Krarup, 1967), intraperitoneal (Krarup, 1967), intravenous (Jull, 1969), or sUbcutaneous routes (Shisa and Nishizuka, 1968) will cause ovarian tumors in mice. Even direct application of DMBA to the ovary has induced tumors (Krarup, 1969).…”
mentioning
confidence: 99%
“…Subsequent studies have shown that the administration of DMBA by oral (Biancifori et al, 1961;Jull et al, 1966;Krarup, 1967), intraperitoneal (Krarup, 1967), intravenous (Jull, 1969), or sUbcutaneous routes (Shisa and Nishizuka, 1968) will cause ovarian tumors in mice. Even direct application of DMBA to the ovary has induced tumors (Krarup, 1969).…”
mentioning
confidence: 99%
“…The reason for this ultimate unilateral development may be found in changes in the hormonal balance (Shisa and Nishizuka, 1968). The role of overstimulation by pituitary gonadotrophins for the development of the tumours has been described after X-irradiation (Miihlbock, 1953) and intrasplenic ovary transplantation (Biskind and Biskind, 1944;Biskind et al, 1953;Lipschutz et al, 1964).…”
Section: Histogenesis Of Ovarian Tumoursmentioning
confidence: 99%
“…THE carcinogenic hydrocarbon 9,10-dimethyl-1,2-benzanthracene (DMBA) administered to sensitive strains of mice affects the ovaries and induces granulosa cell tumours regardless of whether it is applied externally to the skin (Howell et al, 1954;Marchant, 1957; Mody, 1960), orally (Biancifiori et al, 1961;Jull et al, 1966;Krarup, 1967;Kuwahara, 1967), intraperitoneally (Krarup, 1967;Kuwahara, 1967), intravenously (Kuwahara, 1967), subcutaneously (Shisa and Nishizuka, 1968), or directly to the surface of the ovary (Krarup, 1969a).…”
mentioning
confidence: 99%
See 1 more Smart Citation